Efficacy of chlorine dioxide as a disinfectant - Shermaine Yee; Ya Chee Lim; Choon Fu Goh; Vikay Kotra; Long Chiau Ming (Progress in Microbes and Molecular Biology)
Chlorine dioxide plays a significant role in the industrial settings as disinfectants due to its broad antimicrobial property. Despite commonly use as germicide, chlorine dioxide demonstrates a good safety profile, rendering its suitability for use at water treatment and food preparation zones. Protein denaturation including envelope proteins is the major mechanism of chlorine dioxide to inactivate microorganisms even at low concentrations. Adverse reactions are not widely reported due to the typical use at a low concentration. The effectiveness of chlorine dioxide against various microorganisms, in both liquid and gaseous forms, over a wide range of pH and at an extremely low concentration has confirmed chlorine dioxide as a vital and versatile disinfectant.